Utility of nerve conduction studies and ultrasonography in ulnar neuropathies at the elbow of different severity. Issue 7 (July 2020) - Omejec, Gregor; Podnar, Simon
Highlights: Nerve conduction studies were the most sensitive for ulnar neuropathy at the elbow (UNE) diagnosis. Only nerve conduction velocities reflected the clinical severity of UNE. Ultrasonography is the method of first choice for the most severe UNE with hand muscle atrophy. Abstract: Objective: To report the sensitivity and the ability to precisely localize ulnar neuropathies at the elbow (UNE) of different severity by ultrasonography (US) and compare it to standard 10-cm nerve conduction studies (NCSs), and 2-cm short-segment NCSs (SSNCSs) across the elbow. Methods: In a group of consecutive UNE patients, a prospective and blinded study was performed. The evaluation included clinical examination, electrodiagnostic (EDx) and US studies. We compared US and NCSs for sensitivity and the ability to precisely localize the UNE of different clinical severity. Results: We studied 202 affected arms of 197 UNE patients. Clinically very mild UNE was diagnosed in seven, mild in 43, moderate in 99 and severe in 53 arms. The sensitivities of SSNCSs were 14%, 67%, 93% and 100%, of 10-cm NCSs, 29%, 44%, 80% and 96%, and of US 14%, 47%, 59% and 89%, respectively. Precise UNE localization was possible using SSNCSs in 29%, 56%, 78% and 85%, and using US in 29%, 44%, 70% and 98%, respectively. Conclusion: The present study demonstrated that NCSs are more sensitive than US for the diagnosis of UNE of all clinical grades of severity. US was more efficient in localizing clinically severe, and SSNCSs in localizing mild or moderate UNE. Significance: We recommend SSNCSs as the first confirmatory test in UNE across all grades of severity.